Growth performance and meat quality of rice fed broiler and native chicken genotypes in Bangladesh - MA Rahman; MM Hossain; MM Rahman; MS Ali; MA Hossain; MA Hashem (Meat Research, 2022)
The study was conducted on growth and meat quality attributes of rice fed broiler and native chicken genotypes under intensive rearing. A total 360 DOC from two genotypes were reared in a common brooder house. The diet samples were divided into three treatment groups viz. T1 - corn (0% rice), T2 -50% corn replaced by rice and T3 -100% corn replaced by rice. Data were analyzed using 2×3 factorial design. Broiler showed significantly (p<0.01) higher growth performance as compared to native chicken. Cooking and drip loss were significantly (p<0.01) higher in broiler whearas WHC, ultimate pH and cooked pH were significantly (p<0.01) higher in native chicken breast meat. The diet had a significant (p<0.01) effect on water holding capacity (WHC) but the highest WHC% was found in T1 treatment. The CIE L*, a*, b*, was significantly (p<0.01) higher in broiler. The interaction between genotype and diet was found significantly (p<0.05) different in b* in breast and thigh meat; L*, b* in drumstick meat; a* in liver, respectively. The L* and b* were significantly (p<0.05) higher in broiler drumstick meat. The L* and a* values were significantly (p<0.05) higher in liver of broilers. Significantly (p<0.01) higher tenderness and juiciness were found in broiler breast meat than native chicken. This study provides an important insight on growth performance and meat quality of rice fed broiler and native chicken genotypes. Hence, rice could be used as alternative to corn in chicken ration.